2005
DOI: 10.1002/cncr.21190
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation after gamma knife stereotactic radiosurgery of vestibular schwannoma

Abstract: We studied the distributions of interneurons containing the calcium‐binding proteins parvalbumin and calbindin D‐28k, as well as that of pyramidal neurons containing nonphosphorylated neurofilament (NNF), in the middle temporal visual area (MT) of marmoset monkeys. The distributions of these classes of cells in MT are distinct from those found in adjacent areas. Similar to the primary visual area (V1), in MT, calbindin‐immunopositive neurons can be objectively classified into “dark” and “light” subtypes based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 185 publications
(252 reference statements)
4
115
1
4
Order By: Relevance
“…[25][26][27] Although we observed no significant effect of cochlear doses in the current study, this issue deserves further investigation in a larger series.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…[25][26][27] Although we observed no significant effect of cochlear doses in the current study, this issue deserves further investigation in a larger series.…”
Section: Discussioncontrasting
confidence: 63%
“…25 Facial neuropathy, both transient and permanent, occurred in 2.8% of tumor-affected sides in this study. This figure is similar to that of the low-dose treatment group in the study by Rowe et al 11 (Table 3).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Ito et al reported that 69% of patients who underwent radiosurgery (median dose: 16.8 Gy) for acoustic neuroma exhibited pure tone average (PTA) elevation of >20 decibels (dB), suggesting hearing loss after treatment [16]. Similarly, Paek et al reported that 16/25 patients (64%) with serviceable hearing pre-treatment suffered hearing loss of >20 dB after radiosurgery (12 Gy at the 50% isodose) [17].…”
Section: Hypofractionatedmentioning
confidence: 99%
“…Modern singlefraction SRS has been associated with a 10-40% risk of cranial nerve damage in some series [14,15], and the incidence has been reported to be as high as 60% when qualitative hearing assessments are used [16,17]. On the other hand, a conventional fractionated radiation therapy regime with 30-33 treatments over 5-6 weeks is very rarely associated with neurological toxicity [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%